PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI INSTITUT AGAMA ISLAM SAHID - Tuti Artianingsih (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2023)
This study aims to determine the effect of compensation and organizational culture on employee performance at the Sahid Islamic Institute. partially and simultaneously the method used is descriptive quantitative. The population and sample in this study amounted to 44 people. Employees of the Sahid Islamic Institute of Religion. The technique of collecting data is by using a questionnaire, the technical analysis of the data used in this linear is multiple linear analysis. Analysis The research instrument uses SPSS ver 16.0. The results of the analysis consist of several tests, namely the validity test with Pearso Product Moment, all of which are declared valid. With a reliability test using Cronbach's alpha value > 0.6 and all the results are declared reliable. The normality test used the Kolmogorov-Smirnov (K-S) test and all were declared to be normally distributed. The results of the statistical test of multiple linear regression analysis obtained the following regressions: 1) Compensation (Variable X1) has no positive and significant effect on employee performance at the Sahid Islamic Institute. This is explained based on the t-test (T-test). Compensation hypothesis testing (X1) on the Employee Performance variable (Y) shows a significance value of 0.977 which is greater (>) than 0.05. 2) Organizational Culture (Variable X2) has a positive and significant impact on employee performance at the Sahid Islamic Institute. This is based on the Organizational Culture hypothesis testing (X2) on the Employee Performance variable (Y) showing a significance value of 0.000 which is smaller (<) than 0.05. 3) Compensation (X1) and Organizational Culture (X2) Simultaneously influence the performance of employees at the Sahid Islamic Institute. This is based on the F test (f-test) F count of 26,031 with a significance result of 0.000 and F table = F (k; n-k) = F = (2;44-2) = 2.42 The results show that F count is 26,031 greater (>) than 2.42 and the value of sig. of 0.00 is smaller (<) than 0.05. Based on the determination test, employee performance is influenced by compensation and organizational culture by 56%.